Beyond the diffusion limit: Water flow through the empty bacterial potassium channel - Saparov, Sapar M. (National Academy of Sciences, 2004)
Water molecules are constrained to move with K(+) ions through the narrow part of the Streptomyces lividans K(+) channel because of the single-file nature of transport. In the presence of an osmotic gradient, a water molecule requires <10 ps to cross the purified protein reconstituted into planar bilayers. Rinsing K(+) out of the channel, water may be 1,000 times faster than the fastest experimentally observed K(+) ion and 20 times faster than the one-dimensional bulk diffusion of water. Both the anomalously high water mobility and its inhibition observed at high K(+) concentrations are consistent with the view that liquid–vapor oscillations occur because of geometrical confinements of water in the selectivity filter. These oscillations, where the chain of molecules imbedded in the channel (the “liquid”) cooperatively exits the channel, leaving behind a near vacuum (the “vapor”), thus far have only been discovered in hydrophobic nanopores by molecular dynamics simulations [Hummer, G., Rasaiah, J. C. & Noworyta, J. P. (2001) Nature 414, 188–190; and Beckstein, O. & Sansom, M. S. P. (2003) Proc. Natl. Acad. Sci. USA 100, 7063–7068].